Incremental diagnostic value of post-exercise lung congestion in heart failure with preserved ejection fraction. (24th January 2023) - Kagami, Kazuki; Obokata, Masaru; Harada, Tomonari; Sorimachi, Hidemi; Yuasa, Naoki; Saito, Yuki; Kato, Toshimitsu; Wada, Naoki; Adachi, Takeshi; Ishii, Hideki
Abstract: Aims: Lung ultrasound (LUS) may unmask occult heart failure with preserved ejection fraction (HFpEF) by demonstrating an increase in extravascular lung water (EVLW) during exercise. Here, we sought to examine the dynamic changes in ultrasound B-lines during exercise to identify the optimal timeframe for HFpEF diagnosis. Methods and results: Patients with HFpEF ( n = 134) and those without HF (controls, n = 121) underwent a combination of exercise stress echocardiography and LUS with simultaneous expired gas analysis to identify exercise EVLW. Exercise EVLW was defined by B-lines that were newly developed or increased during exercise. The E / e ′ ratio peaked during maximal exercise and immediately decreased during the recovery period in patients with HFpEF. Exercise EVLW was most prominent during the recovery period in patients with HFpEF, while its prevalence did not increase from peak exercise to the recovery period in controls. Exercise EVLW was associated with a higher E / e ′ ratio and pulmonary artery pressure, lower right ventricular systolic function, and elevated minute ventilation to carbon dioxide production ( VE vs. VCO2 ) slope during peak exercise. Increases in B-lines from rest to the recovery period provided an incremental diagnostic value to identify HFpEF over the H2 FPEF score and resting left atrial reservoir strain. Conclusion: Exercise EVLW was most prominent early during the recovery period; this may be the optimal timeframe for imaging ultrasound B-lines. Exercise stress echocardiography with assessments of recovery EVLW may enhance the diagnosis of HFpEF. Graphical Abstract: Graphical Abstract